2017
DOI: 10.1007/s12402-017-0242-9
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant ‘rapid metabolizers’: wrong label, real phenomena

Abstract: This is a review of the empirical literature regarding what has been described anecdotally as patients who are 'rapid metabolizers' of stimulant medication. The authors propose that this is a misnomer used to describe two types of atypical pharmacokinetic patterns of response: high-dose responders, short-duration responders and two types of atypical pharmacodynamics patterns of response: patients who develop either acute or chronic tolerance. The authors propose that use of more precise terminology should faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, the study arm of the mixed salts of a single-entity amphetamine product that went to 37.5 mg and the dexmethylphenidate study that went to 40 mg would be expected to produce even stronger effects on ADHD symptoms. The study of amphetamine/ dextroamphetamine ER that went up to a 60 mg dose stands out as having the most robust maximum dose of the studies reported in terms of expected equivalent effect on ADHD symptoms, and this might account for the unique report of tachycardia in 5% or more of subjects in the mixed 22 ' There are formulations of stimulants approved for ADHD, such as tablet forms of methylphenidate and amphetamine salts, and some brand forms of those compounds, for which FDA-issued adverse event information is not specifically available. The PIs for these agents list typical side effects that occur with these active ingredients but not specific data for these formulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study arm of the mixed salts of a single-entity amphetamine product that went to 37.5 mg and the dexmethylphenidate study that went to 40 mg would be expected to produce even stronger effects on ADHD symptoms. The study of amphetamine/ dextroamphetamine ER that went up to a 60 mg dose stands out as having the most robust maximum dose of the studies reported in terms of expected equivalent effect on ADHD symptoms, and this might account for the unique report of tachycardia in 5% or more of subjects in the mixed 22 ' There are formulations of stimulants approved for ADHD, such as tablet forms of methylphenidate and amphetamine salts, and some brand forms of those compounds, for which FDA-issued adverse event information is not specifically available. The PIs for these agents list typical side effects that occur with these active ingredients but not specific data for these formulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also clear that the effect of these treatments is not the same in all cases. For example, while some patients benefit from pharmacological treatment with stimulant or non-stimulant drugs, there are also patients who do not respond to these treatments [ 12 , 13 , 14 , 15 ]. Similar results are observed with non-pharmacological treatments, for example, with neurofeedback.…”
Section: Introductionmentioning
confidence: 99%
“…Third, environmental changes (e.g., changing schools, parents’ divorce) may result in new or enhanced stressors that may unmask symptoms, thus requiring an increased dose of a medication to treat new or more severe symptoms of ADHD. Fourth, there is the issue of paradoxical decompensation indicating that tolerance to a medication will inhibit the ability of the individual, either physiologically or psychologically, to respond to symptoms without medication (Weiss et al, 2018). For instance, individuals who have taken ADHD medication across several years may not develop coping mechanisms for their symptoms while medicated than the same children with ADHD who were not medicated (Yanofski, 2011).…”
mentioning
confidence: 99%